Scope of Physiotherapy Practice in District Hospitals of the Semi-developed Barisal Division, Barisal, Bangladesh - Sarkar, John Tilock; Khan, Md Jobair; Khan, Atiqur Rahman (Universitas STRADA Indonesia, 2018)
In the developed nations physiotherapist are autonomously participating in the first line and already they are working in the second line treatment alongside with other professionals and the right for the mass population similar to the goal of the public health. The aim of the study was to sort out the real scenario of the development of physiotherapy services as a part of primary health care services including the knowledge and attitude of the general people. A multistage sampling method was selected for conducting the study in districts hospitals of the Barisal division. Result depicted that among the respondents mean age 36.86 Â± 4.558 years and most 33.3% (n= 73) of them were younger age range 21-30 years and interestingly highest 41.55% (n= 91) were graduated with highly significant (x2= 1.196, P= 0.000). 65.3% (n= 143) of patients had knowledge about physiotherapy. Majority of case 41.1% (n= 90) orthopedic (x2= 86.175, P= 0.000) and medical condition stroke ware highest 30.1% (n= 66) statically significant (x2= 1.561, P= 0.000). Due to the awareness maximum, 39.70% (n= 87) came from self-reference and 88.4% (n= 176) received exercise therapy including other electrical modalities. Lowest 8.70% (n= 19) of patient expense > 300 BDT. Treatment right time 60.3% (n= 132). Treatment success rate 69.4% (n= 152). Difficulty to come physiotherapy center 43.8% (n= 96). Some limitation that causes insufficiency in treatment provide; 10.6% patient noted poor timing, 30.7% long witting time, 68.3% (n= 136) unpleasant, 78.9% (n= 157) absence of physiotherapist, 9.5% (n= 19) lack of cooperation. Although that 99.5% patient demand physiotherapy center as close as their range and 60.3% (n=132) satisfied with the treatment. Therefore it is strongly suggested to set up a modern physiotherapy department within the primary health care system with the qualified physiotherapist in community-level also District level hospital